2019
DOI: 10.1680/jmacr.17.00562
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and reinforcement efficiency of carbon nanotubes in cementitious composites

Abstract: Cement pastes reinforced with various concentrations of functionalised and unfunctionalised carbon nanotubes (CNTs) with different aspect ratios were studied in terms of their dispersion and reinforcement efficiency. Mechanical strength was correlated with geometrical characteristics of CNTs, as well as the microstructure of reinforced pastes. Optimal CNTs of 0·05–0·1 wt% were found effective in increasing the flexural and compressive strength of reinforced pastes up to 36% and 27%, respectively. Efficiently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Using these proportions and methodology, Rocha and Ludvig (2018) [9] achieved approximately 50% gain in compressive and splitting tensile strengths at 0.05% of CNTs, suggesting that the optimum range for incorporation of CNTs based on that methodology is close to this ratio. [3] also confirmed that amounts of CNTs, up to 0.10%, were more effective for increasing the flexural and compressive strengths.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Using these proportions and methodology, Rocha and Ludvig (2018) [9] achieved approximately 50% gain in compressive and splitting tensile strengths at 0.05% of CNTs, suggesting that the optimum range for incorporation of CNTs based on that methodology is close to this ratio. [3] also confirmed that amounts of CNTs, up to 0.10%, were more effective for increasing the flexural and compressive strengths.…”
Section: Introductionsupporting
confidence: 63%
“…In order to achieve effective composite preparation, good dispersion and homogeneous distribution of CNTs are essential. The hydrophobic behavior causes CNT agglomerations and the clusters formed by their presence in high amounts can compromise the mechanical properties [2][3][4]. In addition, due to this characteristic, the nanostructured cement composites' strength presents high variability [2], and consequently, reproducibility and statistical analysis are important to the validation of results.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete compositions are presented in Table 3. The CNT content, of 0.1% by weight of cement, was defined considering the results of previous studies [20,22,23] regarding the mechanical characterization of cement pastes and mortars with 0.015-0.1% of the same type of CNT. Concrete mixes were produced in a vertical shaft mixer with bottom discharge.…”
Section: Fine Sand Coarse Sand Fine Gravel Coarse Gravel Water Absorpmentioning
confidence: 99%
“…During the last decade, carbon nanotubes (CNT) have been studied as a reinforcement material for cement-based composites [16][17][18][19][20][21][22][23][24][25][26]. The growing interest in this field comes from the desire to modify the cement matrix at the scale of their main compounds, by taking advantage of the outstanding properties of CNT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation